TRANSLATION IDEOLOGY ON MUALLAF NOVEL: VIEWED FROM PROCEDURE APPLIED - Kuswardani, Yuli (Universitas Mahaputra Muhammad Yamin, 2023)
Muallaf novel contains many cultural terms and concepts that translator was faced with translation ideology, whether translator will maintain cultural concept of source text or adapt it to cultural concept of target text. This choice has implication for the application of translation procedures. This research was focused on two objectives, namely translation procedure used by translator and translation ideology chosen by translator. Researchers used qualitative research as the approach and descriptive qualitative as type of research. Primary data was Muallaf novel by John Michaelson and secondary data were some appropriate journals and related books. Data collecting technique used was documentation. Sample was gained from four subparts of novel. Data analysing technique used was data reduction, data display, and conclusion drawing and verification. First research result indicated that there were 11 procedures used in translating the novel that categorized into foreignization (SL-oriented) including literal, borrowing and calque and other procedures that categorized into domestication (TL-oriented) including free, adaptation, transposition, description, modulation, reduction, amplification and word for word. The finding about procedures was then used to generate second research result which showed that translator applied foreignization and domestication to be carried out in translating novel. The results of this research can provide input and new insights for translators to combine two ideologies rather than to adopt one of two ideologies in order to produce translation that can still reflect cultural aspects of SL while on the other hand readers do not feel if what he is reading is a work of translation. Due to previous researches that use this novel as an object of study this research can add findings from different point of view. This research also become input for next researchers to study translation ideology to improve translation quality.